Breeding of hexaploid triticale for drought resistance - Г. В. Щипак; В. Г. Матвієць; В. М. Плакса; В. Г. Щипак (Plant Varieties Studying and Protection)
Purpose. Analysis of hexaploid triticale breeding process for drought resistance through the use of systemic ecological tests in contrasting conditions. Methods. Dialectical, field, laboratory and statistical ones. Results. Medium-grown (‘Amos’, ‘Nikanor’, ‘Rarytet’, ‘Yaroslava’) and low-stem (‘HAD 69’, ‘HAD 86’, ‘HAD 110’, ‘Timofei’) multiline varieties of winter and alternate hexaploid triticale were developed with higher adaptability, potential yield of 9–12 tons per ha and high bread-making properties. Among the most drought resistant genotypes, such varieties as ‘Amos’, ‘Buket’, ‘Harne’, ‘Markiian’, ‘Kharroza’, ‘Shalanda’, ‘Nicanor’ and ‘Yaroslava’ showed high values of yield, plasticity and stability. Conclusions. The use of interspecific hybridization instead of intergeneric one in hexaploid triticale breeding, together with systemic testing of the hybrid material in contrasting agro-ecological zones, ensured the creation of multiline competitive varieties with an optimal combination of yield and adaptive properties